Adoption of Pharmacogenomic Testing: A Marketing Perspective - Koufaki, Margarita-Ioanna; Karamperis, Kariofyllis; Vitsa, Polixeni; Vasileiou, Konstantinos; Patrinos, George P.; Mitropoulou, Christina (Frontiers in Pharmacology, 2021)
Pharmacogenomics is becoming an important part of clinical practice and it is considered one of the basic pillars of personalised medicine. However, the rate of pharmacogenomics adoption is still low in many healthcare systems, especially in low- or middle-income countries. The low level of awareness of healthcare specialists could be a potential reason due to which pharmacogenomics application is still in a premature stage but there are several other barriers that impede the aforementioned process, including the lack of the proper promotion of pharmacogenomic testing among interested stakeholders, such as healthcare professionals and biomedical scientists. In this study, we outline the available marketing theories and innovation that are applied to personalized medicine interventions that would catalyze the adoption of pharmacogenomic testing services in clinical practice. We also present the current ethical and legal framework about genomic data and propose ways to tackle the main concerns mentioned in the literature and to improve the marketing perspective of pharmacogenomics.